A Frontline Decision Support System for Georgia Career Centers - Randall W. Eberts; Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 2002)
The Workforce Investment Act (WIA) of 1998 emphasizes the integration and coordination of employment services. Central to achieving this aim is the federal requirement that local areas receiving WIA funding must establish one-stop centers, where providers of various employment services within a local labor market are assembled in one location. A major challenge facing staff in these centers is the expected large volume of customers resulting from relaxed program eligibility rules. Nonetheless, resources for assessment and counseling are limited. To help frontline staff in one-stop centers quickly assess customer needs and properly target services, the U.S. Department of Labor has funded development of a Frontline Decision Support System (FDSS). The FDSS is being pilot tested in the state of Georgia where one-stop centers are called Georgia Career Centers. Technical assistance on the project is being provided by the W.E. Upjohn Institute for Employment Research. FDSS is comprised of two main parts: 1) the systematic job search module, and 2) the service referral module. The systematic job search module is a means to undertake a structured search of vacancy listings. The module provides information about a customer's prospects for returning to a job like their prior one, provides a realistic assessment of likely reemployment earnings, identifies occupations related to the prior one, and screens job vacancy listings by region, occupation, and earnings requirements. The service referral module identifies the sequence of activities that most often lead to successful employment for clients with similar background characteristics. This paper documents the strategy and tools implemented to pilot test FDSS within the internet-based Georgia Workforce System. Pilot field operations in Georgia began in the Athens and Cobb-Cherokee Career Centers in July, 2002.
Keywords: J68; J65; J64; H49; 330; Frontline Decision Support; FDSS; Georgia; Eberts; O'Leary